Where does the money go? Assessing the expenditure and income effects of the Philippines' Conditional Cash Transfer Program - S. Quimbo; J. Capuno; Aleli D. Kraft; R. Molato; Carlos Antonio R. Tan (University of the Philippines, School of Economics (UPSE), 2015)
Evaluation studies on conditional cash transfers (CCT) in the Philippines found small if not insignificantly different from zero effects on household consumption. We use propensity score matching to examine how recipients made use of the money they received, taking into account possible changes in recipient behavior. We find evidence of crowding in - CCT households receive higher transfers from other domestic sources as a positive spillover from becoming CCT beneficiaries Poor CCT households tend to lower their dissavings while non-poor beneficiaries become less indebted. We also find evidence of lower income, lower wages, and lower work-related expenses.
Keywords: D12; I38; H53; 330; Conditional cash transfers; household income and consumption; Philippines